Effects of the Rotation on the Mixed Convection Heat Transfer Analysis for the Peristaltic Transport of Viscoplastic Fluid in Asymmetric Channel - Mohaisen, Hatem Nahi; Abedulhadi, Ahmed M. (Iraqi Journal of Science, 2022)
In this paper, we study the impact of the variable rotation and different variable on mixed convection peristaltic flow of incompressible viscoplastic fluid. This is investigated in two dimensional asymmetric channel, such as the density, viscosity, rate flow, Grashof number, Bingham number, Brinkman number and tapered, on the mixed convection heat transfer analysis for the peristaltic transport of viscoplastic fluid with consideration small Reynolds number and long wavelength, peristaltic transport in asymmetric channel tapered horizontal channel and non-uniform boundary walls to possess different amplitude wave and phases. Perturbation technique is used to get series solutions. The effects of different values of these parameters for the axial velocity, stream function, stress, temperature and pressure gradient have been obtained. The impact of these parameters is discussed and illustrated graphically through the set of figures. Numerical results have been computed by using MATHEMATICA software.